Correction: Synthesis, spectroscopy, structures and antimicrobial activity of mixed-ligand zinc(ii) complexes of 5-nitro-salicylaldehyde thiosemicarbazones. (15th January 2018) - Indoria, Shikha; Lobana, Tarlok S.; Sood, Henna; Arora, Daljit S.; Hundal, Geeta; Jasinski, Jerry P.
Abstract : Correction for 'Synthesis, spectroscopy, structures and antimicrobial activity of mixed-ligand zinc(ii ) complexes of 5-nitro-salicylaldehyde thiosemicarbazones' by Shikha Indoria et al., New J. Chem., 2016, 40, 3642–3653.